A case report of breast cancer in silicone-injected breasts diagnosed by an emerging technique of contrast-enhanced mammography-guided biopsy - Cheung, Yun-Chung; Kuo, Wen-Lin; Lee, Li-Yu; Tang, Ya-Chun (Frontiers in Oncology, 2022)
Background: Breast cancer in silicone-injected breast is often obscured by conventional mammography and sonography. Contrast-enhanced magnetic resonance imaging (CE-MRI) is an optimal modality for cancer detection. This case report demonstrates the use of contrast-enhanced spectral mammography (CESM) and CESM guided biopsy (CESM-Bx) to diagnose breast cancer in silicone-injected breast. However, there is no relevant report in the literature. Case Presentation: A 59-year-old woman who received liquid silicone injection for breast augmentation 30 years ago was transferred to our hospital for CE-MRI guided biopsy due to a suspicion of cancer in her right breast. The CE-MRI showed a 3.1 cm irregular enhanced mass and a 1.1 cm circumscribe mass in the upper outer quadrant of the right breast. Unfortunately, the CE-MRI guided biopsy had to wait for a month due to a busy schedule. The CESM revealed two masses that were consistent with CE-MRI findings. CESM-Bx was performed and the patient was diagnosed with invasive lobular carcinoma with an irregular mass and fibro adenoma of the circumscribed mass. The patient underwent substantial surgery. Conclusions: CESM-Bx is a simple emerging technique that can be used feasibly to obtain tissue proof on the concerned enhanced lesion on CESM. In such cases of silicone injected breast, the CESM-Bx can be used as an alternative to MRI guided biopsy for cancer diagnosis.